Penerapan Model Learning Cycle Untuk Meningkatkan Tanggung Jawab Siswa (PTK Pada Kelas V SD Negeri 11 Kota Bengkulu) - Wulanda Rahmadia; Alexon Alexon; Sri Dadi (Universitas Bengkulu, 2020)
This research aims to increase the responsibility of students in grade V to Negeri 11 Bengkulu by applying the Learning Cycle learning model. This research is a classroom action research. The subjects of this study were 28 students consisting of 14 male students and 14 female students. The research procedure is in the form of a cycle. Each cycle consists of four stages including planning, implementing actions, observing and reflecting. The research instrument was in the form of observation sheets of teacher and student activities. The data analysis technique used is the observation sheet using the formula of the average score, the highest score, the lowest score, the difference in score and the range of values for each criterion. Thus the application of the Learning Cycle model can increase the responsibility of VB grade students in Sd Negeri 11 Bengkulu City.